2000
DOI: 10.1016/s0925-4773(00)00306-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell behaviour of Drosophila fat cadherin mutations in wing development

Abstract: We have studied several cell behaviour parameters of mutant alleles of fat (ft) in Drosophila imaginal wing disc development. Mutant imaginal discs continue growing in larvae delayed in pupariation and can reach sizes of several times those of wild-type. Their growth is, however, basically allometric. Homozygous ft cells grow faster than their twin cells in clones and generate larger territories, albeit delimited by normal clonal restrictions. Moreover, ft cells in clones tend to grow towards wing proximal reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 48 publications
8
62
1
Order By: Relevance
“…However, we observe no fat dependent alteration of E-cadherin expression as has been observed in the wing imaginal disk (31), and Crumbs localization and levels appear normal in fat clones (not shown), implying that there is no obvious defect in junctional complex formation. One possible explanation is the excess proliferation that occurs within fat clones, as suggested by previous results (32), and this is consistent with the observation that suppression of hyperproliferation by overexpressing Warts partially suppresses the polarity disruption phenotype (33). fat clones in 18-h APF pupal wings often have higher cell density than surrounding tissue (data not shown).…”
Section: Does Loss Of Fat Disturb Cell Geometry?supporting
confidence: 90%
“…However, we observe no fat dependent alteration of E-cadherin expression as has been observed in the wing imaginal disk (31), and Crumbs localization and levels appear normal in fat clones (not shown), implying that there is no obvious defect in junctional complex formation. One possible explanation is the excess proliferation that occurs within fat clones, as suggested by previous results (32), and this is consistent with the observation that suppression of hyperproliferation by overexpressing Warts partially suppresses the polarity disruption phenotype (33). fat clones in 18-h APF pupal wings often have higher cell density than surrounding tissue (data not shown).…”
Section: Does Loss Of Fat Disturb Cell Geometry?supporting
confidence: 90%
“…6). This is consistent with the fact that Drosophila mutant phenotypes of both ft and ds have short and thick adult legs, despite the fact that ft and ds have distinct expression patterns in Drosophila imaginal discs (Garoia et al, 2000;Ma et al, 2003). These results were not expected if Ds and Ft acted as a traditional ligand and receptor.…”
Section: Formation Of the Ds-ft Gradientsupporting
confidence: 82%
“…In the wing disc, ds is highly expressed in proximal regions, and fj is expressed distally, whereas ft is expressed uniformly throughout the disc (Fig. 4) (Garoia et al, 2000;Mao et al, 2006;Reddy and Irvine, 2008). Since uniform misexpression of Fj and Ds in the wing disc inhibits cell proliferation and growth, graded expression of Ft regulators such as Fj and Ds could modulate Ft signaling by polarizing Ft activity within the cell (Rogulja et al, 2008;Willecke et al, 2008).…”
Section: Relationship Between Morphogen Gradients and The Ds-ft Signamentioning
confidence: 99%
See 1 more Smart Citation
“…Its deletion causes hyperplastic overgrowth of larval imaginal discs, and defects in differentiation and morphogenesis (Bryant et al, 1988;Mahoney et al, 1991). Of particular interest is the fact that FAT interacts with components of the EGFR pathway in Drosophila (Garoia et al, 2000). Sequencing analysis of full-length cDNA revealed that the FAT gene encodes a huge protein (27 exons, 4590 amino acids, 506 kDa) with 34 cadherin-like domains, five EGF-like repeats interspersed with two laminin A-G chain motifs, a transmembrane domain and a novel cytoplasmic domain (Mahoney et al, 1991;Ponassi et al, 1999).…”
Section: Discussionmentioning
confidence: 99%